Space-time trends in fetal mortality in Brazil, 1996–2021 - João Batista Francalino da Rocha; Italla Maria Pinheiro Bezerra; Elyecleyde Katiane da Silva Oliveira; Aline Bergamini Effgen Sena; Francisco Naildo Cardoso Leitão; Luiz Carlos de Abreu (Revista de Saúde Pública)
ABSTRACT OBJECTIVE To evaluate the space-time trend of fetal mortality in Brazil from 1996 to 2021. METHODS Ecological time series study with secondary data on fetal deaths at gestational age (GA) ≥ 20 weeks from the Mortality Information System (SIM) in Brazil, between 1996 and 2021, covid-19 pre-pandemic (1996–2019), and years 2020 and 2021 of the pandemic. It analyzed the fetal mortality rate (FMR) to identify the annual risk of fetal death in the specific population. The percentage change (PC), annual percentage change (APC), and average annual percentage change (AAPC) were calculated using Joinpoint regression to determine the trend patterns: increasing, decreasing, or stationary. Excel 2019, Stata, and Joinpoint Regression software were used. RESULTS In Brazil, fetal deaths at GA ≥ 20 weeks accounted for 1.14% of births and 58% of perinatal deaths in the period analyzed. Around 93% were antepartum, 6% intrapartum, and 1% were recorded as occurring postpartum. The overall FMR for the period, considering GA ≥ 20, ≥ 22, and ≥ 28 weeks, was 11.4, 10.7, and 8.6/1,000 births, respectively. Despite the increasing trend of stillbirths in perinatal deaths, a slowdown in the reduction and an increase during the covid-19 pandemic, the FMR at the gestational ages evaluated decreased by 20%, 25%, and 41%, respectively, with a AAPC of -1.00, -1.13, and -1.89. CONCLUSION Fetal mortality showed a long-term downward trend at the national and regional levels in Brazil, except in the Central-West region, where the trend was stationary. The covid-19 pandemic slowed down the reduction and increased the measure, however, the downward trend was not interrupted. Regionally, the highest FMRs and the smallest reductions occurred in the North, Northeast, and Central-West, showing regional inequalities.